Crimen, disección y metáfora: el caso de la Venus Negra - Rosalina Estrada Urroz (Centre de Recherches sur les Mondes Américains, 2011)
Anatomy was for more than three hundred years ‘a galaxy in expansion’ that moved to other worlds like philosophy and morality, spirituality and literature, or aesthetics and enjoyment. Dissection attributes to the feminine body some characteristics culturally constructed. They are not only expressed in dissection, but in scientific and literary narration. Three cases of homicides of prostitutes, that took place in Puebla and Veracruz, allow us to recover this sinuous relation among diverse speeches involved in crime. In judicial files these cases are reported with details and facts. Declarations are repeated viewing crime evidences. Chronicle uses the literary approach that chains the events, turns it in metaphor and reconstructs the cases. Morality does not escape the arguments that justify the crimes, in the practice of autopsy the characteristics of the victims are explored in veins, entrails and stomach, centering on the heart, organ that moves between nobility and perversion.